Современные тенденции органической химии в университетах России - Негребецкий В. В.; Чупахин О. Н.; Корлюков А. А.; Филимонов В. Д. Виктор Дмитриевич; Краснокутская Е. А. Елена Александровна (2018, 2018)
Заглавие с экрана